PENGARUH PENGALAMAN AUDIT, FEE AUDIT DAN AKUNTABILITAS TERHADAP KUALITAS AUDIT(STUDI PADA KANTOR AKUNTAN PUBLIK DI JAKARTA) - Adelita Novita Sari Arya Ningsih, (2020)
The research aims to analyze the effect of audit experience, audit fees and accountability on audit quality. The sample used in this study is 100 auditors working at KAP in Jakarta registered in the IAPI Directory. Data source is primary data. Data collection methods are using g-forms and questionnaires that are delivered directly to the Public Accountant Office in Jakarta. Data analysis techniques used SmartPLS 3.2.8 with a significance level of 5%. The results of this study indicate that Audit experience has no effect on Audit Quality. Audit Fee has a significant positive effect on Audit Quality. Accountability has a significant positive effect on Audit Quality.